Development of Collaborative Learning in Early Childhood through Gobak Sodor Game - Utami, Trias; Widyasari, Choiriyah (Universitas Muhammadiyah Surakarta, 2023)
Purpose: Collaborative learning in early childhood is important in nurturing a culture of cooperation and teamwork. This research endeavours to introduce children to the traditional game of gobak sodor to cultivate collaboration from an early age. Methodology: This study employs qualitative and data collection methods encompassing interviews, observations, and documentation. This research focused on a cohort of 23 group B students, with detailed observations conducted on a subset of 6 children. Thematic analysis models were utilised for data interpretation. The research protocol includes introductory sessions, exemplification, and practical engagement in gobak sodor gameplay. Results: The findings underscore the efficacy of gobak sodor in fostering collaborative learning among early childhood participants. Beyond enhancing physical motor skills, the game promotes collaborative aptitudes, advocating its integration into pedagogical practices. Applications/Originality/Value: This study underscores the transformative potential of gobak sodor in nurturing early childhood collaborative learning. By engaging in this traditional game, children cultivate values of mutual cooperation, responsibility, strategic thinking, and problem-solving while fostering a sense of communal heritage preservation. Furthermore, the game instils traits of solidarity, loyalty, empathy, and sportsmanship, thereby enriching the socio-emotional development of participating children.